Songwriting Group Music Therapy to promote psychological adjustment in informal caregivers of elderly people with dependency: a mixed methods study - Pérez-Núñez, Paula; O’Callaghan, Clare; López-Paz, Juan Francisco; Ruiz de Lazcano, Aitana; Rodríguez, Alicia Aurora; Amayra, Imanol (Frontiers in Psychology, 2024)
Informal caregivers of elderly people with dependency (EPD) provide intensive care that can affect their quality of life (QoL). Psychosocial interventions such as music therapy are important to work on their self-care. The aim of this study is to analyse, with a mixed method approach, the experience of participating in a Songwriting Group Music Therapy (SGMT) intervention on informal caregivers of EPD.. A total of 11 groups, with a convenience sample of 61 caregivers, received 10 SGMT sessions.Quantitative information related to QoL variables (anxiety, depression, spirituality, burden and coping) was collected before and after the intervention, and at 3 months follow-up. Regarding qualitative data, an open-ended question about the experience of participating was asked. The results showed significant changes, sustained over time, in trait anxiety and depression, and in subscales including inner peace, social functioning and mental health. Three themes were generated from the thematic analysis, including that SGMT participation can enhance personal growth, bring out and enable work on emotions, and promote helpful interpersonal dynamics. Findings indicate that SGMT can be a useful intervention for informal caregivers of EPD, promoting psychological adjustment, enhanced coping, emotional regulation and social support. This study reinforces the findings with caregivers of other populations, providing new results and highlighting the benefits of SGMT for caregivers of EPD.